(untitled) (TAMADDUN NURI JURNALI, 2025)
This article reveals the meaning and essence of the term “Husni Khulk”. Based on the historical-theoretical and scientific-philosophical literature, a comparative analysis of the historical-theoretical, traditional and modern, philosophical interpretation of “Husni Khulk” is carried out. The meaning of the term “Husni Khulk” in ancient civilizations and the exact words used to describe it are mentioned. In different ancient civilizations such as Ancient Egypt, Mesopotamia, Ancient India, China, Greece and Rome, it has a certain meaning and essence, as well as what terms are used to interpret it during the revolution.